The x-linked LSP1α gene of Drosophila Melanogster is not acetylated by MOF, but is sex-specifically regulated by individual components of the MSL complex : a thesis presented in partial fulfilment of the requirements for the degree Doctor of Philosophy in Genetics at Massey University, Palmerston North, New Zealand - Weake, Vikki Marie (Massey University, 2005)
Male Drosophila melanogaster double the transcription of most of the genes on their single X chromosome, to equal that from the two female X chromosomes, in a process termed dosage compensation. This process is mediated by the MSL complex, consisting of both protein and non-coding RNA components. This complex is only active in males due to the presence of MSL2, which is not translated in females. The X-linked Lsp1α gene of Drosophila melanogaster appears to escape dosage compensation, and exhibits two-fold higher levels of expression in females compared to males. The apparent lack of dosage compensation of Lsp1α could be due to the promoter being more active in females than in males, or to a lack of regulation by the MSL complex. In this study, the mechanism by which this happens has been addressed. Lsp1α is expressed exclusively in the fat body tissue of third instar larvae, and forms part of a multi-protein complex that acts as a nutrient reservoir during pupariation. In this study it has been shown that transgenes, in which the reporter gene, lacZ, is under the control of the Lsp1α promoter, exhibit variable levels of increased activity in female compared to male third instar larvae. At high levels of transgene expression, activity of the transgene is equal in female and male larvae. When the expression of the transgene is low, the activity of the transgene is much higher in female compared to male larvae. This increased sensitivity of the Lsp1α promoter to position effects in females appears to be mediated by one or more components of the MSL complex. Females ectopically expressing MSL2 exhibit decreased levels of transgene activity. Furthermore, overexpression of MSL1 causes an increase in the activity of transgenes subject to strong position effects. Despite these findings, the sex-specific regulation of the Lsp1α promoter does not account for the non-dosage compensated appearance of Lsp1α. Instead, unlike control dosage compensated X-linked genes, Lsp1α is not enriched for a histone modification, acetylation of lysine 16 of histone H4 that is essential for dosage compensation by the MSL complex. The developmental stage at which the four genes flanking Lsp1α are expressed has been determined using northern RNA hybridization. Expression of the gene immediately 3' of Lsp1α could not be detected at any developmental stage using northern RNA hybridization or in adults by RT-PCR. However, the two genes flanking Lsp1α are expressed in equal levels in male and female Drosophila as determined by quantitative RNase protection analysis. Furthermore, the regions between Lsp1α and these flanking dosage compensated genes do not prevent dosage compensation of an X-linked armlacZ reporter gene. Bioinformatic analysis shows that Lsp1α is present in three species closely related to D. melanogaster but is absent in more distantly related species. It is probable that because of its recent evolutionary origin, the Lsp1α gene lacks the DNA sequences that are required to attract the MSL complex. More generally, a model is proposed in which dosage compensation involves binding of the MSL complex to DNA sequences in actively transcribed regions with possible limited spreading to closely associated active genes.
Keywords: Fruit fly genetics; Gene expression; Fields of Research::270000 Biological Sciences::270200 Genetics::270201 Gene expression